f(x)=6x, where underset(1)(x)=0 to underset(2)(x)=4 . Find the average rate of change of the function from underset(1)(x) to underset(2)(x)

Anish Buchanan 2021-09-07 Answered
f(x)=6x, where
\(\displaystyle{\underset{{{1}}}{{{x}}}}={0}\to{\underset{{{2}}}{{{x}}}}={4}\)
Find the average rate of change of the function from \(\displaystyle{\underset{{{1}}}{{{x}}}}\to{\underset{{{2}}}{{{x}}}}\).

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Plainmath recommends

  • Ask your own question for free.
  • Get a detailed answer even on the hardest topics.
  • Ask an expert for a step-by-step guidance to learn to do it yourself.
Ask Question

Expert Answer

Sally Cresswell
Answered 2021-09-08 Author has 4161 answers

\(f(x)=6x\)
\(f(0)=6(0)\)
\(=0\)
and
\(f(4)=6(4)\)
\(=24\)
\(\displaystyle\frac{{{f{{\left({4}\right)}}}-{f{{\left({0}\right)}}}}}{{{4}-{0}}}=\frac{{{24}-{0}}}{{4}}\)
\(=6\)
6 is the average rate of change.

Have a similar question?
Ask An Expert
43
 

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more
...